Rattus feliceus Thomas 1920 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus feliceus Thomas 1920 Rattus feliceus Thomas 1920, Ann. Mag. Nat. Hist., ser. 9, 6: 423. Type Locality: Indonesia, Kepulauan Maluku, Pulau Seram, Gunung Manusela, 6000 ft (1830 m). Vernacular Names: Spiny Seram Island Rat. Distribution: Known only from Seram Isl, sea level to 1830 m (Helgen, 2003 b ). Conservation: IUCN – Vulnerable. Discussion: Rattus leucopus species group. Amplified description and comparison with R. koopmani from Peleng Isl provided by Musser and Holden (1991), who also discussed past subspecific allocations of feliceus to other species of Rattus . Phylogenetic affinities of R. feliceus are probably with species of Rattus endemic to New Guinea region (Musser and Holden, 1991), an alliance based upon morphology that should be tested with molecular data. Reviewed by Flannery (1995 b ) and Helgen (2003 b ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1470, DOI: 10.5281/zenodo.7316535